The Challenges of English Teachers in Teaching English at Primary Schools - Falah, Irfan Fajrul; Apsari, Yanuarti; Kusumah, Rita (UNIB Press, 2023)
The transformation of the education curriculum is inevitable since the quality of teaching and learning should be improved. As a part of the curriculum structure, the status of English at the primary level remains the same. It is an optional subject that can be taught based on school readiness and the availability of English teachers. However, given the new look of the curriculum that emphasizes students' interest and needs in learning, it is worth investigating on what challenges that faced by the teachers in its implementation. In addition, the study on the challenges of the Merdeka Curriculum Implementation particularly in teaching English has not been voiced loudly by other researchers. Therefore, this study is aimed at figuring out the challenges faced by English teachers. The research employs an exploratory case study research design. The participants of the study were Six English teachers (two males and four females) who teach English in the first and fourth grades of elementary schools. The data of this study was collected through interviews. The result of the study showed that dealing with the implementation of the Merdeka Curriculum English teachers had the challenges related to internal and external aspects. Internal aspects including teachers’ qualification, students’ vocabulary and motivation. While, external aspects cover limited time allotment, Limited opportunity in joining Merdeka curriculum Champaign, limited school facilities, and Lack of professional development programs. These findings should be concerned, not only by the teachers but also it is the responsibility of schools and government to solve those issues. Therefore, the quality of teaching English at the primary level could be better in the future.